A subunit vaccine Ag85A-LpqH focusing on humoral immunity provides substantial protection against tuberculosis in mice - Lingyuan Zeng; You Zuo; Minghui Tang; Chengrui Lei; Huoming Li; Xiuling Ma; Jiahong Ji; Hao Li (iScience)
Summary: The importance of humoral immunity in combating TB has gained extensive recognition. In this study, a subunit vaccine named Ag85A-LpqH (AL) was prepared by fusing the antigen Ag85A proved to induce robust T cell immune responses, and LpqH was shown to produce protective antibodies. The prevention and BCG prime-boost mouse models were established to test the vaccine efficacy. The results indicate that Ag85A-LpqH can induce substantial protection by reducing bacterial loads and pathological lesions. This vaccine can induce robust antibody responses, as well as T cell immune responses especially strong CD8+ T cell responses. Moreover, the serum from AL-immunized mice can reduce the bacterial load and lung pathology in mice. B cell receptor (BCR) sequencing revealed a notable rise in BCR diversity among mice immunized with AL. These results indicate that Ag85A-LpqH can be a promising vaccine candidate for tuberculosis prevention and control.